Radiation shielding design for sealed radioactive gamma-ray and neutron sources: measurements and modeling - Mahanyapane, Motlatsi Vincent (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.